The Influence of Origami and Rectangular Crash Box Variations on MPV Bumper with Offset Frontal Test Examination toward Deformability - Imam Kusyairi (University of Muhammadiyah Malang, 2017)
Crash Box attached between bumper and chassis of a car serving as a kinetic energy absorber during the collision. In previous research, origami pattern crash box was tested at low speed, high speed, and frontal impact and oblique impact directions. They resulted predictable collapse and stable deformation patterns. It is directly proportional to the energy absorption during the impact. Origami pattern crash box was modeled in square but it cannot be used if it is applied in MPV car, the geometry is unsuitable to the bumper and chassis. Therefore, in this research, the crash box designed according to the size of bumper and chassis of MPV car where its shape is rectangular on the surface. This research will compare the deformation pattern between origami and rectangular crash box adapted to conditions and dimensions of the MPV car. Design built using CAD software and simulation is performed using FEM (Finite Element Method) software. Simulation test modeled with impactor, bumper and crash box, while offset frontal test with 16 km/h impact speed conducted using material bilinear isotropic hardening modeling. Result show that origami pattern crash box has predictable deformation pattern than rectangular pattern crash box.